Pyrgopsella (Cirripedia: Balanomorpha: Pyrgomatidae) is not a sponge-inhabiting barnacle - Achituv, Yair; Simon-Blecher, Noa (Zootaxa, 2006)
A new species of coral-inhabiting barnacle, Pyrgopsella youngi, is described. It was found in a colony of the coral Symphyllia radians Milne Edwards & Haime, 1849 from Sulawesi, Indonesia. The barnacles were suspended in the coral tissue and were easily detached. A unique feature of Pyrgopsella is its membranous basis; in P. youngi the calcareous basis is reduced to a vestige by which the barnacle is attached to the coral. Pyrgopsella has been regarded as a genus of sponge-inhabiting barnacle, thus unique in the otherwise coral-associated family Pyrgomatidae, but our findings confirm that this genus too comprises coral-inhabiting barnacles. We propose a new genus, Pyrgospongia, to accommodate the sponge-inhabiting barnacle originally described as Pyrgopsella stellula Rosell, 1973. The relationships of both Pyrgopsella and Pyrgospongia within the Pyrogomatidae are discussed.